Significados atribuidos a la comunicación, jerarquía y relaciones parentales de una familia con hijo adolescente que presenta perdida del año académico: un estudio de caso (2020)
The present study aims to describe the meanings attributed to communication, hierarchy and parental relationships by a mother with a teenage daughter who has low academic performance. In the case study, there was the participation of a 52 year old parent who currently lives with her partner and daughter. Therefore the analysis of five categories was established by means of qualitative matrices, two of them emerging, which respond to the objectives set at the start of the investigation. The information was collected through an unstructured interview, which allowed the communication to be identified in the narrative, significant parental hierarchies and relationships in the family system with a teenager who had lost academic year. Limited and ineffective communication was found between members, diffuse hierarchies and management of power-sharing among the family and conflictive and distant parental relationships with minimal capacity to seek appropriate solutions.